1995
DOI: 10.1128/cdli.2.2.156-159.1995
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and preliminary evaluation of a low-molecular-mass antigen preparation for improved detection of Helicobacter pylori immunoglobulin G antibodies

Abstract: Previously, immunoglobulin G (IgG) antibodies to five antigens with a relative molecular mass of between 15 and 30 kDa from Helicobacter pylori were found to be significantly more frequent in H. pylori-infected patients than in noninfected patients. In this study, these specific low-molecular-mass (LMW) antigens were separated by ultrafiltration of whole-cell sonicates. The LMW antigen preparation was evaluated by enzymelinked immunosorbent assay with serum samples from 76 children with abdominal symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…A recent French study of pediatric patients also found the highest concordance index for the 26 kDa band [30]. Andersen et al suggested a combination of the 19-36 kDa bands to identify H. pylori positive patients [31,32], which was supported by the high concordance indexes for the low molecular bands in our study and also in the French study [30].…”
Section: Discussionsupporting
confidence: 88%
“…A recent French study of pediatric patients also found the highest concordance index for the 26 kDa band [30]. Andersen et al suggested a combination of the 19-36 kDa bands to identify H. pylori positive patients [31,32], which was supported by the high concordance indexes for the low molecular bands in our study and also in the French study [30].…”
Section: Discussionsupporting
confidence: 88%
“…We have reported the serum immunoglobulin G immune reaction to H. pylori crude antigens in gerbil models with the early and advanced stages of H. pylori infection [20]. The results with gerbils appear to correlate with results obtained from humans [13,14,23]. The antibody response in-patient with H. pylori infection includes a response to high-molecular proteins (110/120 kDa), medium-size proteins (43-66 kDa) and low-molecular-mass proteins (26,29,30,31 and 33 kDa).…”
supporting
confidence: 56%
“…In recent years, serological studies have shown that patients with H. pylori infection develop elevated levels of specific anti-H. pylori antibodies, and several antigens specific for H. pylori have been identified [11][12][13][14][15]. Using serum from the H. pylori -infected Mongolian gerbils model [16,17], which mimics human disease [18,19], we have reported the serum immune response and screened for H. pylori antigens [20] in this model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…History of dyspepsia, peptic ulcer or other gastrointestinal disease, smoking and alcohol intake habits was recorded. The control group consisted of 110 age-and sex-matched in-patients (56 females and 54 males; median age, 57.2; range, 30-89 years), admitted to Kaunas Medical University Hospital and Vilnius Oncology Centre for illnesses unrelated to gastrointestinal disorders: diabetes mellitus (21), miscellaneous gynaecological disorders (23), osteoporosis (3), pneumonia (10), hemiparesis (14), glaucoma (16), cataract (11), coronary heart disease (12). Tumour staging was based on the histopathological (pTNM) classification system [9].…”
Section: Patientsmentioning
confidence: 99%